2017
DOI: 10.1080/09544828.2017.1376244
|View full text |Cite
|
Sign up to set email alerts
|

The design platform – a coherent platform description of heterogeneous design assets for suppliers of highly customised systems

Abstract: This paper has been peer-reviewed but does not include the final publisher proof-corrections or journal pagination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 24 publications
1
40
0
Order By: Relevance
“…In more recent publications, the topic of modularization is dealt with in the context of mass customization. André et al present an industry study on platform design that combines views of both the platform and finished products (André et al 2017). Pakkanen et al have identified the most important engineering concepts in this field using the so-called 'Brownfield Process' in order to be able to implement modularization and the creation of product families in a mass customization environment: partitioning logic, set of modules, interfaces, architecture and configuration knowledge (Pakkanen et al 2016).…”
Section: Methods For Modularization and The Development Of Modular Kitsmentioning
confidence: 99%
“…In more recent publications, the topic of modularization is dealt with in the context of mass customization. André et al present an industry study on platform design that combines views of both the platform and finished products (André et al 2017). Pakkanen et al have identified the most important engineering concepts in this field using the so-called 'Brownfield Process' in order to be able to implement modularization and the creation of product families in a mass customization environment: partitioning logic, set of modules, interfaces, architecture and configuration knowledge (Pakkanen et al 2016).…”
Section: Methods For Modularization and The Development Of Modular Kitsmentioning
confidence: 99%
“…For products within the ETO-oriented production strategy working with fluctuating requirements this is not surprising and similar findings have been observed previously (Jansson 2013;Jensen 2014). As André et al (2017) stated, for platforms in an ETO-context, coherence across all disciplines in needed, which aligns with the basic principles of lean where long-term strategy and holistic view are cornerstones. Modularisation offers an entry to efficiency but active work in all domains is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…This is typically done by using a set of common components which are shared between product variants at the same time as varying distinctive components (variant components) to produce product variants which are differentiated by the market. André et al (2017) introduce a design platform that should support the development of customised products, where coherence across all disciplines is emphasised.…”
Section: Theoretical Framework Platform Theorymentioning
confidence: 99%
“…The DP (André et al, 2017) was created as a response to the lack of platform models for ETO companies; especially as a means to increase the reuse of company assets in environments where requirements fluctuate during the development. A DP is composed of different objects related to Process, Synthesis Resources, Product Constructs, Assessments Resources, Solutions, Projects and Constraint.…”
Section: The Design Platform Approachmentioning
confidence: 99%